The Radicalism Prevention Policy in State Islamic Religious Universities in South Sulawesi: An Overview of Maqasid Syari'ah - Lukman Arake; Ismail Keri; Syawaluddin Hanafi (IAIN Manado, 2021)
This study aims to raise the perspective of Islamic law on the policy of preventing radicalism at PTKIN in South Sulawesi, which is by dharuriyyat al-khamsah in maqasid shari'ah. This research is qualitative research with a maqasid sharia approach with data collection methods obtained through documentation and interviews. The results of this study found that; First, The stipulation of the Chancellor's Decree regarding the ethics committee and appointing several lecturers from the leadership element, as well as the involvement of senior lecturers providing an understanding of peace and Islam as a religion of rahmatan lilalamin, then supervising academic activities, having strict, active, and consistent duties in carrying out ethics committee sessions, considered capable of preventing radically oriented behaviour. Second, build the image of the campus as a centre for Islamic studies and Bugis culture. Third, to provide room for discussion, both through seminars and face-to-face, especially with students exposed to radicalism. Fourth, make a study of Religious Deradicalization, which aims to prevent radicalism and strengthen religious moderation. When viewed from the perspective of maqaṣhid shari'ah, some of these efforts in preventing radicalism in several PTKIN in South Sulawesi are very important to determine as the main factor in efforts to deradicalize religion and also religious moderation. As relevant to the values of maqaṣhid shari'ah, which uses some of its features, namely universality, the interplay of hierarchies, and openness (freedom of the academic pulpit).